KONTRIBUSI SEKTOR PERTANIAN PADA PERTUMBUHAN EKONOMI DI PROVINSI JAWA BARAT - Wiwin Widianingsih; Any Suryantini; Irham Irham (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2015)
This study aims to know the trend of GDRP of agricultural sector in West Java Province, sector and sub-sector of agriculture which has a role as a leading sector in West Java Province and each district in this province, the factors that affect the economic growth of agriculture sector in the West Java Province, and the growth typology of the agricultural sector in West Java Province. The method that used for this study are Trend analysis, Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift-Share, and Klassen Typology. Theresults showed that the trend of agriculture sector/sub-sectors’ GDRP value were significantly increased and the trend of agriculture sector/sub-sectors’ GDRP contribution were significantly decreased over the period year 2003-2012. The agricultural sector is a leading sector for West Java Province and most of its districts. Food crop and the horticultural sub-sector is a leading sector for West Java Province and some districts in this province. The growth of the national economy is the dominant factor affecting the growth of the sector/subsector of agriculture in West Java Province. The competitive advantage (competitiveness) of forestry sub-sector was higher than the same sub-sector in other areas at national level. Food crops and horticultural sub-sector and livestock sub-sector were advanced ut depressed sub-sector. Forestry sub-sectors was categorized in developing sub-sector. The agriculture sector, plantation and fisheries sub-sector were categorized in lagging development. Based on LQ, DLQ and Klassen Typology analysis, the results showed that there was a consistent result that were the forestry sub-sector categorized in a leading sub-sector in the future, f ood crops and horticulture sub-sector categorized in leading sub-sector along year 2003-2012. While sector of agriculture, plantation and fisheries sub-sector categorized in the lagged development sectors.